Giant Flexomagnetoelectric Effect in Dilute Magnetic Monolayer. Issue 8 (26th June 2018) - Shen, Yu‐Hao; Song, Yu‐Xi; Tong, Wen‐Yi; Shen, Xin‐Wei; Gong, Shi‐jing; Duan, Chun‐Gang
Abstract: Spintronics rooted in the spin degree of freedom is of both theoretical and technological importance. The development of some fantastic properties for electrically controlling this degree of freedom encourages enormous effort to the research on magnetic systems which possess sensitive magnetic response to the electric field. Here, a giant flexomagnetoelectric effect is predicted in a typical dilute magnetic monolayer Mn‐doped MoS2 . Combining lattice bending and magnetic doping, it is shown that the magnetic response and magnetic anisotropy can be greatly amplified under the applied electric field. Further investigations reveal that such an effect stems from the orbit‐dependent response of the single magnetic dopant. Physically, the electric field‐induced orbital polarization causes the spatial distribution change of the Mn‐3d orbital wavefunction, which is sensitive to the change of the orbital hybridization with the bent lattice. Hence the corresponding 3d energy levels can be controlled to shift near Fermi level via external electric field. These findings open a new route toward functional 2D materials design for flexible devices. Abstract : In the Mn‐doped MoS2 monolayer with highly bending curvature, both the magnetic response and magnetic anisotropy are predicted to be greatly amplified under the applied electric field. The induced orbital polarization causes the spatial distribution change of the Mn‐3d orbital wavefunction, which is sensitive to the change of the orbital hybridization with the bent lattice. Such a giant flexomagnetoelectric effect can be attributed to the orbit‐dependent response of the single magnetic dopant.